1990
DOI: 10.2307/1982134
|View full text |Cite
|
Sign up to set email alerts
|

A Troubled Future?: Participation in Postsecondary Education by Youths with Disabilities

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Among students reporting a disability, 41 percent reported a learning disability, 22 percent said they had other disabilities, 19 percent indicated they had a health-related disability, 13 percent indicated they were partially sighted or blind, 12 percent were hearing impaired, 9 percent had orthopedic or physical impairments, and 5 percent had speech impairments (Henderson, 1999). Students with sensory impairments (hearing, visual) showed the highest rates of participation in postsecondary education, whereas young adults with multiple impairments (for example, visual and hearing, speech and mobility) were least represented among the collegegoing population (Fairweather and Shaver, 1990;HEATH, 1999). One reason for the lack of documentation of students with multiple disabilities on college campuses is directly attributable to data-gathering techniques.…”
Section: Demographic Trends In Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among students reporting a disability, 41 percent reported a learning disability, 22 percent said they had other disabilities, 19 percent indicated they had a health-related disability, 13 percent indicated they were partially sighted or blind, 12 percent were hearing impaired, 9 percent had orthopedic or physical impairments, and 5 percent had speech impairments (Henderson, 1999). Students with sensory impairments (hearing, visual) showed the highest rates of participation in postsecondary education, whereas young adults with multiple impairments (for example, visual and hearing, speech and mobility) were least represented among the collegegoing population (Fairweather and Shaver, 1990;HEATH, 1999). One reason for the lack of documentation of students with multiple disabilities on college campuses is directly attributable to data-gathering techniques.…”
Section: Demographic Trends In Educationmentioning
confidence: 99%
“…Public two-year institutions enroll more than half of all college students reporting a disability (National Center for Education Statistics, 1999;Phillippe, 1997); students with disabilities account for 8 percent of the total enrollment at two-year institutions (Barnett and Li, 1997;Phillippe, 1997). Enrollment of students with disabilities at four-year institutions is considerably lower than at two-year colleges, except among students with visual impairments (Fairweather and Shaver, 1990). Although enrollment of students with disabilities at four-year institutions has increased in the past decade (Henderson, 1999), most students with disabilities who enter two-year institutions are not transferring to a four-year institution and pursuing a baccalaureate degree (National Center for Education Statistics, 1999).…”
Section: Demographic Trends In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that students with health impairments who enter higher education typically are older, are more likely to live at home, have lower educational expectations, are more likely to enroll in 2-year than 4-year schools, have lower rates of acceptance into selective universities and enroll in fewer classes than students without health impairments (Fairweather & Shaver, 1990;Janus, 2009;Luna, 2009;Sanford et al, 2011;Wells, 2003;Vogel & Adelman 1992). We address these issues by, first, controlling on living arrangements and age.…”
Section: The Role Of Social Integration and Enrollment Characteristicsmentioning
confidence: 99%
“…The fastest growing segment of students with disabilities attending postsecondary institutions has been and continues to be students with learning disabilities (Shaw & Norlander, 1986;Yost, Shaw, Cullen, & Bigaj, 1994). Fairweather and Shaver (1990) suggested that a major factor in the transition from high school to adulthood for students with disabilities is the access and success in postsecondary education and training. They suggested that, in general, two mechanisms are used to facilitate this access.…”
mentioning
confidence: 99%